PELATIHAN PENERAPAN TEKNOLOGI IRIGASI TETES SEDERHANA UNTUK MEMPRODUKSI BUAH SALAK GULA PASIR DI LUAR MUSIM - IN RAI; IW WIRAATMAJA; CGA SEMARAJAYA; ING ASTAWA; IM SUKEWIJAYA; N ARI MAYADEWI; G WIJANA (Buletin Udayana Mengabdi, 2015)
Natural flowering of “Salak Gula Pasir” occures once every three months or 4 times a year, however, only oneto two of flower season succeeds to become fruit. Failure fruit-set causes the fruit harvest seasonally; partly due tothe internal water content of leaf is low. The situation is not favorable in terms of agribusiness because productionquantities accumulate only during the harvest time (on-season). Off-season flowering technology of “Salak GulaPasir” by simple dripping irrigation has been founded, gardeners, however have not yet recognised. The aim ofthis community service is to introduce that technology by means of training to the gardeners. The participantsattended the training seriously because the subject was really expected by them. After training, participants wereconvinced that they can do how to make off-season production of “Salak Gula Pasir”, moreover they expect thelocal government would provide rainwater harvesting and the required dripping irrigation installations.Keywords: salak Gula Pasir, drip, irrigation, off-season, training.